OXIDATION AND POLYMORPHISM OF FATTY ACIDS AND NUTRITIONAL ASPECTS CONJUGATED OF LINOLEIC ACIDS - Mohammad Asif (Indonesian Journal of Pharmacy, 2013)
Fats and oils are triglycerides containing one unit of glycerol with three units of fatty acids. It also contained mono- and diglycerides, phosphatides, cerebrosides, sterols, terpenes, fatty alcohols, free fatty acids, fat-soluble vitamins, and other substances. Fats and oils are recognized as essential nutrients in both human and animal diets. They provide the most concentrated source of energyand also provide essential fatty acids which are precursors for important hormones. Conjugated linoleic acid (CLA) is a group of geometrical and positional isomers of linoleic acid. In contrast to linoleic acid, double bonds in CLA are usually located at positions 9 and 11 or 10 and 12 and each double bond can be either in the cis or trans configuration. Meat and dairy products from ruminant animals are the principal natural sources of CLA in the human diet. Dietary CLA has been shown to have potent anti-carcinogenic, antiatherogenic, immune modulating and also have other biological activities. The CLA was also reported to reduce body fat content.Key words: anti-atherogenic, anticarcinogenic, conjugated linoleic acid, Fats and oils, immune modulator